1983
DOI: 10.1143/jjap.22.l567
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Polythiophene Battery

Abstract: A secondary battery utilizing polythiophene films as cathode and anode active materials in an electrolyte of TBABF4/MeCN is studied. The cell potential, energy density and maximum power density (based on the weight of cathode and anode films) are observed to be 3.1 V, 93 Wh/kg and 89 kW/kg, respectively, for the dopant concentration of 24 mol%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
81
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(85 citation statements)
references
References 4 publications
3
81
0
1
Order By: Relevance
“…The synthesis of the lithium methoxy oligo (oxyethylene) sulfonate (LiSEO 7 The monomer was prepared by etherification of methoxy oligo (oxyethylene) with allyl chloride with a modified procedure. To a well-stirred mixture solution of methoxy oligo (oxyethylene) (take M w ϭ 350, n ϭ 7 as example) 35 g (0.1mol), 0.2 g tetrabutylammoiumiodide, and aqueous 50% (w/w) sodium hydroxide 10 g (0.125 mol NaOH), allyl chloride 38 g (0.5mol) was added at 70°C within 1 h. After the reaction was completed, the mixtures were extracted by ether until the oil phase become colorless.…”
Section: Experimental Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the lithium methoxy oligo (oxyethylene) sulfonate (LiSEO 7 The monomer was prepared by etherification of methoxy oligo (oxyethylene) with allyl chloride with a modified procedure. To a well-stirred mixture solution of methoxy oligo (oxyethylene) (take M w ϭ 350, n ϭ 7 as example) 35 g (0.1mol), 0.2 g tetrabutylammoiumiodide, and aqueous 50% (w/w) sodium hydroxide 10 g (0.125 mol NaOH), allyl chloride 38 g (0.5mol) was added at 70°C within 1 h. After the reaction was completed, the mixtures were extracted by ether until the oil phase become colorless.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…4 -6 However, some investigations have demonstrated that the ionic conductivity occurs only in the amorphous regions of the PEO 7 , while a high proportion of the crystalline regions will greatly reduce the total conductivity. In view of that, there have been a number of works on synthesizing polymer hosts for the sake of giving fully amorphous polymer electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Potential applications of conducting polymers such as polyaniline (PANI), polypyrrole (PPY) and poly thiophene (PTP) in batteries [1][2][3][4], electronic devices [5][6][7][8], displays [9], sensors [10], electrodes [11], electronic tongue [12], nanotubes or nanorods [13] and molecular electronics [14][15][16][17] are well known. There are mainly two routes for the preparation of CPs: chemical and electrochemical polymerization [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Conducting polymers with π-electron conjugated systems such as polyacetylene, polypyrrole, polythiophene and their analogues adopt neutral, oxidized, and reduced states [1][2][3][4]. The oxidized and reduced states are both highly conductive.…”
Section: Introductionmentioning
confidence: 99%